Serum sickness-like reaction to sulfamethoxazole-trimethoprim. - Aldeia da Silva, R.; Nunes, A.S.; Antunes, A.; Neves, I.M. (European Journal of Pediatric Dermatology, 2024)
A 6-year-old girl with recurrent otitis media developed a serum sickness-like reaction (SSLR) following a 10-day course of sulfamethoxazole-trimethoprim (SMX-TMP). Symptoms included a pruritic rash, joint pain with edema, fever, and eye congestion, which worsened within 24 hours. Laboratory investigations ruled out infectious causes, and the diagnosis was confirmed based on the timing and clinical presentation.